HUBUNGAN STATUS MENYUSUI DENGAN PRODUKSI ASI - Rice Noviawanti (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Breastfeeding is recommended exclusively for 6 months and continued for 2 years, the many advantages and benefits of breastfeeding are still indicated by the coverage of breastfeeding less than 100%, namely 69.7% in 2021. Many things are a factor in the low coverage of breastfeeding, one of which is the mother's ability to produce breast milk. well. This study aims to determine the relationship between maternal breastfeeding status and the amount of milk production. This study is a quantitative analytical descriptive study through a scrosectional approach with a chi-square test taken through secondary data as many as 30 populations and samples. The test results obtained p value (0.045) which means that there is a significant relationship between breastfeeding status and milk production.